Physical, Chemical and Microbiological Quality of Opaque-Plastic Bottled Drinking Water Distributed in Chon Buri Province, Thailand - Nimrat, Subuntith; Jitaree, Apinya; Vuthiphandchai, Verapong (Journal of Applied Research on Science and Technology (JARST), 2021)
This study was conducted to assess physical quality (label information, water characteristic, odor, manufacturing date/expiry date (MFD/EXD), and pH), chemical quality (total solids) and microbiological quality (coliform and fecal coliform bacteria, E. coli) of 45 opaque-plastic bottled drinking water sold in Mueng district, Chon Buri province. All tested opaque-plastic bottled drinking water products were clear, odorless, and had pH and total solid values ranging from 5.53-7.51 and 1.0-147.0 mg/L, respectively. In addition, all samples represented coliform and fecal coliform bacteria less than 2 MPN/100 mL and were devoid of E. coli. In accordance with the standard for drinking water in sealed container imposed by Ministry of Public Health, opaque-plastic bottled drinking water (8 samples; 17.8%) did not meet the criterion because of pH values lower than standard value (6.5–8.5). Also, all drinking water samples (100%) did not abide by the standard due to the absence of MFD/EXD on the labels with the presence of only label information related to company name and place of manufacture. Therefore, consumers should consciously choose the opaque bottled drinking water products with guarantee of quality.